Estratégias de enfrentamento na disfonia em diferentes modalidades terapêuticas - Almeida, Larissa Nadjara Alves (2016)
When diagnosed with dysphonia there are needed strategic cognitive and behavioral adjustments, in order to control the consequences of the change and the stress caused by the condition, called coping strategies. These are listed by the dysphonic individual to reduce the impact of vocal disorders, and assist them in seeking treatment. It is known that speech therapy is a treatment with scientific evidence for rehabilitation of dysphonia, through different therapies, direct, indirect and eclectic approaches, and different modalities, individual and group therapy. The latter is currently described as effective in the treatment of dysphonia, in addition to promoting the sharing among participants and creating solutions to cope the health problem. This study aimed to verify the effectiveness of group therapy and individual, due to increased coping strategies in dysphonia. For this, an applied research was carried out, field, analytical and quantitative, approved by the Research Ethics Committee with Humans, of the CCS / UFPB. The study included 70 subjects divided into two groups, group therapy (TG) and individual treatment (IT), seeking speech therapy at the Clinical School of Speech Therapy of the Federal University of Paraíba (UFPB). We used the Vocal Screening Protocol (PTV) to collect personal data of the participants and the Coping Strategies Protocol in dysphonia (PEED), with their scores: Total (T), Focus on Problem (FP) and Focus on Emotion (FE) for information on how they face dysphonia. Student's t test and Chi-square association - descriptive and inferential statistical analysis was performed through the software R. The results showed that overall TG and TI were homogenous, since most of patients were women (73%; n=27 and 72,7%, n=24), non-voice professionals (64,9%, n=24 and 75,8%; n=49), who had slit glottal or lesion in the membranous portion of the vocal fold (64,8%; n=24) and (48,5%; n=16). Participants of TG and TI initially used an average of 54,32 (±16,78) and 55,45 (±19,60) coping strategies to dysphonia, respectively. Group treatment in the PEED scores improved, achieved total gain of 7,59 (±19,00), 4,21 (±7,99) improvement in the focus on the problem and gain of 3,64 (±13,38) in focus on emotion. When compared the average scores of PEED domains pre and post-therapy, it was observed significant improvement in TG in T scores (p=0,03) and FP (p=0,02) demonstrated its effectiveness in relation to coping dysphonia. TI did not show significant improvement. In addition, women (74,1%; n=20) had a higher gain in relation to coping than men (30,0%; n=3) in the TG. Individuals with behavioral dysphonia group had higher post-therapy gain, glottis (75,0%; n=9) and lesion in the membranous vocal folds (58,3%; n=7), and these post-therapy recent improved only in relation to the focus on the issue. In TG, the gender variable influences the total score (p=0,014) and laryngeal diagnosis in the score focus on emotion (p=0,038). Thus, it is concluded that group therapy is effective in helping patients to increase the coping strategies in dysphonia. Sex and laryngeal diagnosis influence the gain for voice group post-therapy coping strategies. Women with behavioral dysphonia are the people most benefited by group therapy.